VALIDATION OF THE DEVELOPED COMMUNICATIVE LEARNING MATERIAL FOR IGBO L2 LEARNERS AT THE UPPER BASIC LEVEL IN EBONYI STATE - Nwigwe, Nwakaego; Obeka, Ngozi O (EBSU Journal of Social Sciences and Humanities, 2023)
This study was carried out with the aim of validating the communicative learning material developed for learners of Igbo as a second language at the upper Basic level in Ebonyi State. Four purposes and four null hypotheses guided the study. The design of the study was a descriptive survey research design. The population and the sample of the study was 150 Igbo learners and teachers. The instrument for data collection was researchers structured questionnaire designed in 4-point rating scale to elicit responses from the respondents. The data analysis was done using mean and standard deviation and t-test statistics. Analysis of findings indicate no significant difference in the perceptions of Igbo L2 learners and teachers as to the adequacy and appropriateness of the learning materials for the target group. Based on the findings, some recommendations were made.